FAKTOR PERSEPSI WISATAWAN DALAM KEPUTUSAN BERWISATA DI GLAMPING LAKESIDE RANCABALI, BANDUNG, JAWA BARAT - Kusumaningrum, Dewi Ayu (Jurnal Pendidikan dan Perhotelan (JPP), 2022)
Tourist needs related to lodging are very important to be considered by tourism producers. Convenience, complete facilities, optimal service and affordable prices are the keys to successfully meeting tourist needs. the reason for choosing accommodation is no longer just wanting to take a vacation. Another thing that is no less supportive to create a memorable vacation. One of them is by choosing the unique concept accommodation offered, which can be a special attraction that will make the trip unforgettable, such as the Glamping Tent which is a unique hotel in the form of large tents that function as rooms. For several years, the Glamping Lakeside tourism object has been operating, it has several problems including social impacts on the surrounding tourism business actors, promotions that do not reach the broad consumer market, limited accessibility and facilities. Apart from the problems faced, Glamping Lakeside Rancabali has become one of the favorite tourist attractions for tourists while on vacation in West Java. The formulation of the problem from this research are; How are Tourist Perceptions in Traveling Decisions at Glamping Lakeside Rancabali?. Descriptive quantitative research method with a questionnaire to collect data containing statements with a Likert Scale. The sampling technique is purposive sampling with the criteria of tourists who have traveled and choose Glamping Lakeside Rancabali tourism for the last 3 years. Descriptive statistical data analysis method; validity, reliability, mean and crosstab. The results showed that in general the mean tourist perception seen from environmental, personal, social and technological factors was positive. The results of the crosstab test of the respondent's profile with the questionnaire statement obtained that respondents with female gender answered agree more, the age of respondents aged 17-25 years mostly answered agree, high school education level most answered agree, profession students most agreed, income below Rp.2,000,000,-.Most of the respondents agreed with the statement of the questionnaire.